PENDEKATAN ARSITEKTUR DENGAN RETHINKING TYPOLOGY DAN DISPROGRAMMING DALAM MERANCANG PUSAT REHABILITASI KECANDUAN GAME - Garry Gohtandry; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
Addiction to online games in this era is increasing. Data shows that in 2017, according to Amsterdam-based marketing research institute Newzoo, there were 43.7 million gamers (56% of whom were male) in the country, spending a total of US 880 million. Indonesia has the largest number of game players in Southeast Asia, with an estimated prevalence of 6.1% of gamers experiencing addiction, so there are 2.7 million game players who may be addicted. The World Health Organization (WHO) officially states that online game addiction is a mental disorder, because it can cause sleep disorders that affect the body's metabolic system, often feel tired (fatigue syndrome), stiff neck and muscles, to Carpal Turner Syndrome. But playing online games also has many positive sides, such as players being trained between the right and left brain to work in a balanced way. Not only that, colorful game visuals and in-game movements provide high imagination so that the brain will continue to imagine. To be able to improve the mental health of online game addicts, a new type of rehabilitation facility is needed that is able to answer the needs and challenges of the times. Considering that addiction generally occurs because of neglecting to play online games for a long time as a child, it is proposed to add an elementary school function that introduces good information technology from an early age. Disprogramming strategy is used so that the rehabilitation function as the first function can contaminate the elementary school as the second function so that these two facilities can function more optimally. This facility is also equipped with a large open space to accommodate social activities as a supporting activity that can teach the importance of real socializing among others. It is hoped that the combination of rehabilitation functions, elementary schools and active open spaces can become a new typology of rehabilitation buildings that reduce the adverse effects of online addiction in society. Keywords: game addiction; online game; rehabilitation center AbstrakKecanduan game online di masa ini semakin meningkat. Data menunjukkan pada 2017, menurut lembaga riset pemasaran asal Amsterdam, Newzoo, ada 43,7 juta gamer (56% di antaranya laki-laki) di negeri ini, yang membelanjakan total US 880 juta. Indonesia memiliki Jumlah pemain game terbanyak di Asia Tenggara, dengan prakiraan prevalensi 6,1% pemain game mengalami kecanduan, maka terdapat 2,7 juta pemain game yang mungkin kecanduan. Organisasi Kesehatan Dunia (WHO) resmi menyatakan bahwa kecanduan game online merupakan penyakit gangguan mental, karena dapat menyebabkan gangguan tidur sehingga mempengaruhi sistem metabolisme tubuhnya, sering merasa lelah (fatigue syndrome), kaku leher dan otot, hingga Karpal Turner Syndrome. Namun bermain game online juga memiliki banyak sisi positif seperti para pemain seperti dilatih antara otak kanan dan kiri untuk bekerja secara seimbang. Tidak hanya itu, visual game yang berwarna warni dan Gerakan dalam game memberikan imajinasi yang tinggi sehingga otak akan terus berimajinasi. Untuk dapat memperbaiki kesehatan mental pecandu game online, dibutuhkan sebuah tipe baru fasilitas rehabilitasi yang mampu menjawab kebutuhan dan tantangan zaman. Mengingat kecanduan pada umumnya terjadi karena adanya pembiaran bermain game online dalam durasi panjang semasa kecil, maka diusulkan untuk menambahkan fungsi sekolah dasar yang mengenalkan informasi teknologi yang baik sedari dini. Strategi Disprogramming digunakan agar fungsi rehabilitasi sebagai fungsi pertama dapat mengkontaminasi sekolah dasar sebagai fungsi kedua sehingga kedua fasilitas ini dapat berfungsi lebih maksimal. Fasilitas ini juga dilengkapi dengan ruang terbuka yang luas untuk mewadahi aktivitas bersosialisasi sebagai aktivitas pendukung yang dapat mengajarkan pentingnya bersosialisasi nyata diantara sesama. Diharapkan penggabungan fungsi rehabilitas, sekolah dasar dan ruang terbuka aktif dapat menjadi sebuah tipologi baru bangunan rehabilitasi yang mengurangi dampak buruk kecanduan online di masyarakat.